1994
DOI: 10.1111/j.1476-5381.1994.tb14864.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by central postsynaptic α2‐adrenoceptors of the jaw‐opening reflex induced by orofacial stimulation in rats

Abstract: 1The modulation by x2-adrenoceptors of the jaw-opening reflex (digastric electromyographic responses) elicited by orofacial electrical stimulation (OF-JOR) in pentobarbitone anaesthetized rats was investigated. 2 Increasing doses of clonidine (0.1-1000 tgkg-', i.v.) reduced, in a dose-dependent manner until abolition, the amplitude and duration of the OF-JOR and increased the latency to onset. The sum of amplitudes of the reflex was the most sensitive parameter to the inhibitory effects of clonidine (ED50 =13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…This could be due to a certain state of activation of the postsynaptic a 2 -adrenoceptors which regulate the OF-JOR elicited by the endogenous NE released during the Þrst minutes after exposure to this stressor. In this context, we have previously observed a dose-dependent reduction of the basal amplitude of the reßex after amphetamineinduced endogenous NE release (García-Vallejo et al 1994). More speciÞcally, after acute tail pinch, an immediate enhancement of NE extracellular levels in hippocampus, amygdala, prefrontal cortex and hypothalamus has been reported, although the levels rapidly returned to their basal values (Kálen et al 1989;Tanaka et al 1991;Finlay et al 1995;Shibasaki et al 1995).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This could be due to a certain state of activation of the postsynaptic a 2 -adrenoceptors which regulate the OF-JOR elicited by the endogenous NE released during the Þrst minutes after exposure to this stressor. In this context, we have previously observed a dose-dependent reduction of the basal amplitude of the reßex after amphetamineinduced endogenous NE release (García-Vallejo et al 1994). More speciÞcally, after acute tail pinch, an immediate enhancement of NE extracellular levels in hippocampus, amygdala, prefrontal cortex and hypothalamus has been reported, although the levels rapidly returned to their basal values (Kálen et al 1989;Tanaka et al 1991;Finlay et al 1995;Shibasaki et al 1995).…”
Section: Discussionmentioning
confidence: 93%
“…DMC 25, Medelec Limited, Survey, UK). The methodology described by García-Vallejo et al (1994), with minor modiÞcations, was followed for both stimulation and recordings. In all experiments, two initial recordings were obtained in the absence of the drug to assess the basal value of the OF-JOR.…”
Section: Experimental Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…For the evaluation of the effects of the drugs on the α 2 ‐adrenoceptors, the parameter sum of amplitudes (Σ amplitude) was evaluated as, in a former study, it had been observed that this is the most sensitive for evaluating the inhibitory effect of clonidine and presents the best correlation coefficient (22). The Σ amplitude was defined as the arithmetical addition of each peak‐to‐peak value of every wave that formed the configuration of the reflex.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%